Power Quality Improvements in Power Electronics-Based Equipment: A Insight into the Research Problem-Part II - Rajashekher Koyyeda; T. C. Manjunath (Journal of Power Electronics and Devices, 2020)
In this 2nd part of the research paper, a brief review of the power quality improvements in power electronics-based equipment – an insight into the problem is presented in a nutshell. Here, how the power can be improved, i.e., the quality of the power which deteriorates due to the continuous switching on & off of the different types of loads is presented concisely. The paper serves as a shot in the arm for the researchers who want to work in the field of power electronics. The 2nd part of the paper is presented in this context here.